The effect of the Mediterranean Diet on lifespan: a treatment-effect survival analysis of a population-based prospective cohort study in Southern Italy. (6th November 2020) - Campanella, Angelo; Misciagna, Giovanni; Mirizzi, Antonella; Caruso, Maria Gabriella; Bonfiglio, Caterina; Aballay, Laura R; Vas de Arruda Silveira, Liciana; Bianco, Antonella; Franco, Isabella; Sorino, Paolo; Buongiorno, Claudia; Cisternino, Anna Maria; et al.
Abstract: Background: The Mediterranean diet (MedDiet) is associated with good health. We aimed to estimate the effect of levels of adherence to the MedDiet on lifespan by performing treatment effects survival analysis. Methods: A sample of 5250 subjects aged ≥18 years were randomly selected from the electoral list of Castellana Grotte and Putignano (Apulian Region, Italy). Cohorts were enrolled in 2005–06 and followed-up until December 2018. The adherence to the MedDiet was measured by the relative Mediterranean score (rMED) and categorized as high, medium and low. Time-to-death (all-causes) as estimated by average treatment effect on the treated (ATET), potential outcome mean (POM) and relative efficiency of exposure were the outcomes. Results: A total of 4896 subjects were included. The median follow-up time was 12.82 (inter quartile range (IQR) 12.22–13.05), 12.91 (IQR 12.21–13.27) and 12.84 (IQR 12.19–13.03) years for high, medium and low rMED subjects respectively. By December 2018, 453 (9.25%) had died. There was a strong effect of medium and low rMED ATET, −5.10 [95% confidence interval (CI) −9.39, −0.80] and −8.91 (95%CI −13.37, −4.45), respectively. High rMED has an important effect on mean age at death [POM 90.16 (95% CI 86.06, 94.25)]. The relative effect size for medium and low rMED subjects was a lower lifespan of 5.62% (95% CI 1.01, 10.3) and 9.90% (95% CI 5.30, 5.30), respectively. Conclusions: We observed an important benefit in additional years of survival from adherence to MedDiet in this southern Italian cohort. Further investigation corroborating our findings in other population groups in other geographic regions will be an important contribution to promoting health and longevity.